Converging or Diverging: Shifting Ethnoracial Composition and the Urban-suburban Distinction in Attitudes toward Immigrants in Houston, 1995–2016. (August 2018) - O'Connell, Heather A.; Raker, Ethan J.
We examine the political position of the suburbs relative to the city by focusing on attitudes toward immigrants. Using 22 years of survey data for the Houston area, this paper addresses three questions. First, how has the attitudinal position of the suburbs relative to the city changed over time? Second, does the city-suburb distinction differ depending on the respondent's race/ethnicity? Finally, do these results differ depending on the content of the question? Multivariate results indicate an overall increase in positive attitudes, but the increase is slower in the suburbs relative to the city. The resulting divergence is driven exclusively by non-Hispanic whites and is only evident when focusing on more contentious questions regarding immigrants in the United States. Our results suggest a persistent suburban cultural context despite recent demographic shifts, and they highlight the multidimensional nature of the (racialized) attitudes toward immigrants held by non-Hispanic whites in the United States.